Respuesta de cuatro variedades de “cebolla colorada” (Allium cepa), a la fertilización con fósforo - Coello Márquez, José David (2017)
VII. SUMMARY The present experimental work was developed on the farm "Hda. New "owned by Mrs. Narcisa Márquez Ramírez, located in the" El Cuatro "sector of the La Unión de Clementina parish, of the Babahoyo county, province of Los Ríos. The zone is located at 277438.26 UTM of west longitude and 110597.97 UTM of South Latitude. Seeds of the Burguesa, Dulcinea F1, Francisca and Osaka F1 varieties obtained from the Alaska importer were used as seed material. The silver targets were to know the answer of the onion to the fertilization with phosphorus, to determine the optimum dose of phosphorus that generates greater yield of the crop and to analyze economically the treatments evaluated, under the open field system. The treatments were conformed by the Factor A varieties of red onions such as Bourgeois, Dulcinea F1, Francisca, Osaka F1 and Factor B Dosage kg / ha of N + P2O5 + K2O, as 100 kg / ha of N + 150 kg / ha of P2O5 + 100 kg / ha of K2O; 100 kg / ha of N + 120 kg / ha of P2O5 + 100 kg / ha of K2O; 100 kg / ha of N + 80 kg / ha of P2O5 + 100 kg / ha of K2O. The experimental design of randomized complete blocks was used in a 4 x 3 factorial arrangement and three repetitions. All variables were subjected to analysis of variance to determine the statistical difference between treatments, using the Tukey test at 95% probability. All the agricultural practices that are applied in the cultivation of red onion for their normal development were carried out, such as planting in the nursery and disinfection, preparation of the land, transplant, irrigation, weed control, phytosanitary control, fertilization and harvest. To estimate the effects of the treatments, the data of leaf analysis, plant height, weight of 10 bulbs, equatorial and polar diameter of the bulb to harvest, yield in kg / ha and economic analysis were taken. From the results obtained it was determined that the four varieties of "red onion" (Allium cepa) responded to phosphoric fertilization, in a different way; the highest plant height was presented in the Burquesa onion variety, applying as fertilization 150 kg / ha of P2O5 + 100 kg / ha of N + 100 kg / ha of K2O; the weight of 10 bulbs reached the highest average with the Francisca variety using 120 kg / ha of P2O5 + 100 kg / ha of N + 100 kg / ha of K2O and 100 kg / ha of N + 80 kg / ha of P2O5 + 100 kg / ha of K2O; the Osaka F1 variety obtained the largest equatorial diameter and the Dulcinea F1 variety with the largest polar diameter of the bulb, both using 100 kg / ha of N + 80 kg / ha of P2O5 + 100 kg / ha of K2O, although this did not favor the yield and the highest yield of the crop was reported by the Dulcinea F1 variety with the application of 100 kg / ha of N + 120 kg / ha of P2O5 + 100 kg / ha of K2O; with this variety the highest net profit was also achieved with $ 2555.49.